Prioritization of delayed vaccination for pandemic influenza - Eunha Shim (Mathematical Biosciences and Engineering)
Limited production capacity and delays in vaccine development aremajor obstacles to vaccination programs that are designed tomitigate a pandemic influenza. In order to evaluate and compare theimpact of various vaccination strategies during a pandemic influenza, we developed an age/risk-structured model of influenzatransmission, and parameterized it with epidemiological data fromthe 2009 H1N1 influenza A pandemic. Our model predicts that theimpact of vaccination would be considerably diminished by delays invaccination and staggered vaccine supply. Nonetheless, prioritizing limited H1N1 vaccine toindividuals with a high risk of complications, followed byschool-age children, and then preschool-age children, would minimizean overall attack rate as well as hospitalizations anddeaths. This vaccination scheme would maximize the benefits ofvaccination by protecting the high-risk people directly, andgenerating indirect protection by vaccinating children who are mostlikely to transmit the disease.